(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
The study aims at gaining insights of the awareness of information privacy among young generation specifically in Malaysia. As we know the awareness should not only be focused on the adults and professionals only but have to be delivered to the young generation also. The knowledge and understanding on the importance of information privacy would help from the occurrence of data breach and privacy intrusions. The youngster should be taught and explained how to keep their data safe and secure from third party interventions. Young children who are unprepared to protect themselves from online risks are likely to encounter individuals who wish to target them emotionally or financially. Bullied children may be more vulnerable to fraud as they are taken advantage of when they seek friendship online. Combating child identity fraud requires guardians to proactively manage their child‟s finances by regularly monitoring activity, even when they expect that nothing has occurred; reviewing statements online and leveraging account alerts, especially those that can be delivered to mobile devices. This paper has used literature review analysis in fulfilling the study aims. As the information privacy issues becomes the highlight in recent news, the access to the existing data are widely available. The findings show that the lack of awareness on the fundamental of Internet knowledge has increased the number of cases in Internet scams, online harassment, cross-site scripting and identity theft. Malaysia has recorded 10,000 cases of cyberbullying in 2018 and the cases increasing day by day. A comprehensive and relevant legal framework should be strengthened time to time in combating the issues.